(untitled) (Religious dialogue and cooperation, 2023)
Institutional education of young people for religious dialogue and tolerance in the Republic of Serbia began with the introduction of optional teaching subjects Religious Education and Civic Education in primary and secondary schools in 2001. At the same time, a radical reform of the educational system was started in accordance with neoliberal ideological principles and development strategies. Explicit and hidden religious and political contents can also be observed in many other teaching subjects that have undergone reform changes in teaching contents, especially in primary education. Religious education is conducted according to the confessional model for recognized churches and traditional religious communities living in Serbia. As a general goal of Religious Education, it was pointed out that it should provide students with a complete religious view of the world and life, as well as enable them to freely adopt the spiritual and life values of the Church or community to which they belong. Then, that this goal should be achieved in an open and tolerant dialogue, with respect for other religious experiences and views. In the tasks of Religious Education, it is indicated that it should develop in students the aspiration towards responsible shaping of common life with other people, peoples, religious communities and cultures different from their own. On the other hand, Civic Education is defined as education for democracy and civil society. The main goal of teaching in this subject is to acquire knowledge and develop skills for the role of a responsible citizen for life in a democratically organized and humane society based on respect for human and civil rights, the right to diversity and the development of multiculturalism. The teaching content in these, as well as in other complementary subjects, has been influencing the formation of basic value attitudes and rules of behavior for two decades, thus creating a new religious and political culture among young people that contributes to a more tolerant attitude towards many social issues and a better understanding of various social phenomena and relationships. It is a well-founded assumption that young people studying in Serbia have the educational potential for religious dialogue and tolerance.